THE ROLE OF PLAY ACTIVITIES IN REDUCING RMD IN CHILDREN OF HYPERACTIVITY - Zainab Ali Kazam Kamas, Dr. Abdul Salam gawdat AL- Zubaidi, Dulaimi Prof Dr.Nahida Abdul Zaid AL (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The current study aimed to know ’’ The role of play activities in reducing RMD in children of hyperactivity’’ The study was conducted in lraq /DhiQar Governorate, Where the researcher adopted the descriptive curriculum as it is the appropriate approach to the research procedures, and the research community consisted of children of excess activity in the primary stage in the first and second grade of primary school to be the sample of the research, to achieve this, To achieve this researcher built a scale for kinetic disorders, and the scale consists of(30) paragraphs distributed over two areas, and each field has a group of (15) paragraphs and after extracting psychometric properties from (validity and consistency) was applied to the basic sample , the researcher used the appropriate statistical means for the researcher procedures(Pearson correlation coefficient, Kay square2, T-test for one sample, and paragraph discrimination coefficient), the results of the research showed the superiority group in the research in order to reduce their motor disorders , and in the light of the research results the researcher came out with a set of conclusions, recommendations and proposals complementary to the current research.